Graphene composite film with high thermal conductivity as well as preparation method and application of graphene composite film

By preparing a graphene film on a copper-nickel alloy substrate and coating a graphene oxide slurry, carbide and graphitization treatment, forming a graphene composite film with high thermal conductivity, solving the insufficient thermal conductivity of graphene films in the prior art. and the problem of difficult transfer, efficient heat dissipation performance and low-cost production are achieved.

CN119136504APending Publication Date: 2024-12-13SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411300188.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to improve the thermal conductivity of graphene films without increasing production difficulty and cost, and the graphene film prepared by CVD method is thin in thickness and difficult to transfer, which cannot meet the heat dissipation needs of electronic devices.

Method used

The graphene film is prepared on a copper-nickel alloy substrate by CVD method, and the surface is coated with graphene oxide slurry. Through carbonization, graphitization and calendering treatment, a graphene composite film with high thermal conductivity is formed, and the pagoda-shaped The multi-layer graphene structure serves as a template to improve the crystallinity and electrical and thermal conductivity of the material.

Benefits of technology

The thermal conductivity and thickness of the graphene film are improved, the transfer difficulty and cost are reduced, the heat dissipation needs of electronic devices are met, and the excellent performance of graphene materials is fully utilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136504A_ABST
    Figure CN119136504A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene composite film with high thermal conductivity and a preparation method and application thereof. The preparation method comprises the following steps: preparing a graphene film on a copper-nickel alloy substrate by adopting a CVD (Chemical Vapor Deposition) method; wherein the graphene film comprises a single-layer graphene structure and a pagoda-shaped multi-layer graphene core structure dispersed on the surface of the single-layer graphene structure; applying the graphene oxide slurry to the surface of the graphene film so as to form a graphene / graphene oxide composite film; and carrying out carbonization, graphitization and calendaring treatment on the graphene / graphene oxide composite film to prepare the graphene composite film with high thermal conductivity. The method not only solves the problems that the graphene film prepared by the traditional CVD method is thin in thickness and cannot be commercially used on a large scale, but also improves the heat-conducting property of the graphene film prepared by the oxidation-reduction method, and fully exerts the intrinsic characteristics of the graphene material, so that the graphene film has higher market competitiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal conductive films, and in particular relates to a graphene composite film with high thermal conductivity and a preparation method and application thereof. Background Art

[0002] With the continuous popularization and application of 5G communication technology, the rapid development of information technology, artificial intelligence, the Internet of Things and other fields, the integration of single electronic devices is becoming higher and higher, and the power density is rapidly increasing while the size is shrinking, which puts higher requirements on the heat dissipation performance and stability of heat dissipation materials. Compared with traditional metal thermal conductive and heat dissipation materials, carbon-based thermal conductive films have become the new mainstream in the thermal conductive market due to their low density and high thermal conductivity.

[0003] According to the raw materials used in production, carbon-based thermal conductive films can be divided into three categories: natural graphite films, artificial graphite films, and graphene films. The preparation methods of graphene films include chemical vapor deposition (CVD), oxidation-reduction method, and the like. The CVD method usually uses metal materials as the substrate to form a thin film by cracking the carbon source material, dissolving the carbon in the substrate, and then precipitating it. The obtained graphene film has a high degree of crystallinity and good thermal conductivity (1000-3000 W / mK), but is very thin (0.33-3.0nm), has low heat flux, and is difficult to transfer the film, making it difficult to commercialize. The oxidation-reduction method usually uses graphene oxide as the main raw material, and prepares a graphene thermal conductive film through pulping, coating, thermal reduction, calendering, and other processes. The thickness of the graphene film can be controlled by adjusting the coating thickness and the number of calendering layers (1-1000μm). It has high heat flux and is easy to transfer. It is currently the main technical solution for large-scale production of graphene films. Related products have been widely used in many fields such as mobile phones, laptops, and communication base stations. However, the degree of crystallinity and thermal conductivity (800-1800W / mK) of the graphene film obtained by this method are not as good as those of the CVD method, and the excellent properties of graphene materials have not been fully utilized.

[0004] Based on the redox method, the existing technical solutions improve the thermal conductivity of graphene films by adding a second component, increasing the graphitization temperature, extending the graphitization time, and multiple heat treatments. Although these methods can improve the thermal conductivity to a certain extent, they greatly increase the difficulty and cost of production. For example, adding a second component will involve many problems such as slurry dispersion uniformity and viscosity changes, and the problem of component removal must also be considered; increasing the graphitization temperature and extending the graphitization time will increase energy consumption and reduce the number of times the carrier is used. The above methods all use a high temperature and high pressure environment to spontaneously transform graphene oxide from disorder to orderly crystallization, and the crystal region structure and crystal size are still inferior to the CVD method. Although the CVD method can obtain high-quality graphene films, the film thickness is thin and the heat flux is low, which makes it difficult to meet the heat dissipation requirements of electronic devices. In addition, the technical difficulty and process of transferring CVD graphene films from substrates are high, the transfer yield is low, and the cost is high. Summary of the invention

[0005] The main purpose of the present invention is to provide a graphene composite film with high thermal conductivity and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: An embodiment of the present invention provides a method for preparing a graphene composite film with high thermal conductivity, comprising: A graphene film is prepared on a copper-nickel alloy substrate by a CVD method; wherein the graphene film comprises a single-layer graphene structure and a pagoda-shaped multi-layer graphene core structure dispersed on the surface of the single-layer graphene structure; applying a graphene oxide slurry to the surface of the graphene film to form a graphene / graphene oxide composite film; Furthermore, the graphene / graphene oxide composite film is subjected to carbonization, graphitization and calendering treatment to obtain a graphene composite film with high thermal conductivity.

[0007] The embodiment of the present invention also provides a graphene composite film with high thermal conductivity obtained by the aforementioned preparation method.

[0008] The embodiments of the present invention also provide uses of the aforementioned graphene composite film with high thermal conductivity in the fields of electronic heat dissipation, aerospace, medical equipment or new energy.

[0009] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses high-crystallinity graphene grown by CVD as a substrate, coats graphene oxide slurry on the graphene surface, and utilizes the template effect of high-crystallinity graphene to induce graphene oxide to repair defective structures and crystallize and grow at high temperatures, thereby obtaining a graphene film with a more regular structure, increasing the film thickness while further improving the thermal conductivity of the film; at the same time, the multi-point pagoda-shaped multilayer graphene will induce the graphene oxide to rearrange and assemble into a graphene structure under high-temperature conditions of graphitization. This pagoda-shaped multilayer graphene structure is an excellent template material. Based on this, a graphene material with a higher degree of crystallinity and a more regular structure can be epitaxially grown, further improving the electrical and thermal conductivity of the material; (2) In the present invention, the metal substrate is gasified and removed at the high temperature of graphitization, which solves the problem of difficult peeling and transfer of graphene prepared by the original CVD method; (3) In the present invention, the metal substrate forms metal vapor during the evaporation process, which helps the catalytic cracking and recombination of carbon atoms, forming a graphene structure with fewer defects, and facilitating the epitaxial growth of graphene. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1 is a schematic diagram of a preparation process of a graphene composite film with high thermal conductivity in a typical embodiment of the present invention; Figure 2 Optical microscope image of pagoda-shaped graphene in Example 1 of the present invention; Figure 3 This is an optical microscope image of a single-layer graphene in Comparative Example 1 of the present invention; Figure 4 It is a scanning electron microscope image of the cross section of the graphene composite film in Example 1 of the present invention. DETAILED DESCRIPTION

[0012] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The present invention first controls the process conditions of preparing graphene film by CVD method, grows a graphene film with a single-layer graphene structure and a multi-point pagoda-shaped multi-layer graphene core on a copper or copper-nickel alloy substrate, and then applies graphene oxide slurry on the copper substrate with the special structure graphene film, and then performs drying, carbonization and graphitization, calendering and other steps to prepare a graphene composite film with high thermal conductivity. The growth of pagoda-shaped multi-layer graphene is mainly controlled by substrate composition, gas flow rate and ventilation time. Experiments show that nickel substrates are relatively easy to form multi-layer graphene structures, while copper substrates are more suitable for growing single-layer graphene. By adjusting the copper and nickel content of the substrate material, a multi-point pagoda-shaped graphene structure can be achieved. Further, the production of high heat flux graphene thermal conductive film is achieved by preparing graphene thermal conductive film by traditional graphene oxide slurry.

[0013] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0014] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a graphene composite film with high thermal conductivity includes: A graphene film is prepared on a copper-nickel alloy substrate by a CVD method; wherein the graphene film comprises a single-layer graphene structure and a pagoda-shaped multi-layer graphene core structure dispersed on the surface of the single-layer graphene structure; applying a graphene oxide slurry to the surface of the graphene film to form a graphene / graphene oxide composite film; Furthermore, the graphene / graphene oxide composite film is subjected to carbonization, graphitization and calendering treatment to obtain a graphene composite film with high thermal conductivity.

[0015] In some preferred embodiments, the schematic diagram of the preparation process of the graphene composite film with high thermal conductivity of the present invention is as follows Figure 1 shown.

[0016] In some preferred embodiments, the preparation method specifically comprises: Placing a copper-nickel alloy substrate in a tube furnace, introducing a first atmosphere, and pre-treating the substrate at 800-1100° C. for 10-200 min; wherein the first atmosphere comprises any one of hydrogen, argon, and a hydrogen-argon mixed gas; and the gas flow rate of the first atmosphere is 10-500 sccm; And, a carbon source gas and an inert gas are introduced into the device and graphene is deposited and grown on the substrate surface at 800-1100° C. for 1-30 minutes, thereby obtaining a graphene film; wherein the flow rate of the carbon source gas is 1-100 sccm, and the flow rate of the inert gas is 0.5-100 sccm.

[0017] Furthermore, the copper content in the copper-nickel alloy substrate is 50-98wt%.

[0018] Furthermore, the bottom layer diameter of the pagoda-shaped multilayer graphene core structure is 0.1-5 mm.

[0019] Furthermore, the number of layers of the pagoda-shaped multilayer graphene core structure is 4-10.

[0020] Furthermore, the height of the pagoda-shaped multilayer graphene core structure is 1.3-3.4 nm.

[0021] Furthermore, when the first atmosphere is a hydrogen-argon mixed gas, the volume content of hydrogen in the first atmosphere is 1-80%.

[0022] Furthermore, the carbon source gas includes any one or more combinations of ethylene, propylene, acetylene, methane, and ethanol, but is not limited thereto.

[0023] Furthermore, the inert gas includes any one or more combinations of nitrogen, argon, and helium, but is not limited thereto.

[0024] In some preferred embodiments, the preparation method specifically comprises: Mixing graphene oxide with water and adjusting the pH value to 5-10 with ammonia water to form graphene oxide slurry; wherein the solid content in the graphene oxide slurry is 2-7wt%; And, the graphene oxide slurry is coated on the surface of the graphene film and dried at 40-105° C. to obtain a graphene / graphene oxide composite film, wherein the coating thickness coated on the surface of the graphene film is 0.5-5.0 mm.

[0025] Furthermore, the pH value is 6-8.

[0026] Furthermore, the solid content of the graphene oxide slurry is 4-5wt%.

[0027] Furthermore, the temperature of the drying process is 60-80°C.

[0028] Furthermore, the coating thickness is 2.5-3.5 mm.

[0029] In some preferred embodiments, the preparation method specifically includes: heating the temperature to 80-400°C at a heating rate of 0.5-5°C / min and performing low-temperature treatment on the graphene / graphene oxide composite film in a low-temperature atmosphere for 30-120min, then heating the temperature to 800-1500°C at a heating rate of 1-20°C / min and performing carbonization treatment in a medium-temperature atmosphere for 30-240min, then heating the temperature to 2700-3200°C at a heating rate of 1-20°C / min and performing graphitization treatment in a high-temperature atmosphere for 30-600min; wherein the low-temperature atmosphere includes air and / or nitrogen; the medium-temperature atmosphere includes any one or more combinations of nitrogen, argon, and a hydrogen-argon mixture; the high-temperature atmosphere includes argon.

[0030] Furthermore, the heating rate used in the low temperature treatment is 0.5-1°C / min.

[0031] Furthermore, the temperature of the low temperature treatment is 200-300°C.

[0032] Furthermore, the low temperature treatment time is 60-90 minutes.

[0033] Furthermore, the low temperature atmosphere is air.

[0034] Furthermore, the heating rate used in the carbonization treatment is 5-8°C / min.

[0035] Furthermore, the temperature of the carbonization treatment is 850-1050°C.

[0036] Furthermore, the carbonization treatment time is 60-120 minutes.

[0037] Furthermore, the medium temperature atmosphere is a hydrogen-argon mixed gas, wherein the volume content of hydrogen in the hydrogen-argon mixed gas is 5-10%.

[0038] Furthermore, the heating rate used in the graphitization treatment is 3-6°C / min.

[0039] Furthermore, the temperature of the graphitization treatment is 3000-3200°C.

[0040] Furthermore, the graphitization treatment time is 120-180 minutes.

[0041] In some preferred embodiments, the calendering treatment is performed by roller pressing and / or flat pressing, but is not limited thereto.

[0042] In some preferred embodiments, the pressure used in the calendering process is 10-200 MPa.

[0043] In some more specific embodiments, the method for preparing the graphene composite film with high thermal conductivity comprises the following steps: (1) Using copper-nickel alloy as the substrate for graphene growth, the substrate is cut into a suitable size and placed in a tube furnace, hydrogen, argon or a mixture of the two is introduced to pre-treat the metal substrate, and then a mixture of carbon source gas and inert gas is introduced to deposit and grow graphene to obtain graphene foil. The pre-treatment temperature is 800-1100°C, the time is 10-200 min, the gas flow rate is 10-500 sccm, and the hydrogen content in the mixed gas is 1-80%; the temperature for graphene deposition and growth is 800-1100°C, the growth time is 1-30 min, the carbon source gas used includes ethylene, propylene, acetylene, methane, ethanol, etc., with a flow rate of 1-100 sccm, and the inert gas used includes nitrogen, argon, helium, etc., with a flow rate of 0.5-100 sccm.

[0044] (2) Using the foil on which graphene is successfully grown in step (1) as a substrate, a pre-prepared graphene oxide slurry is coated on the surface, and then dried to obtain a graphene / graphene oxide composite film. The preparation process of the graphene oxide slurry is as follows: disperse the graphene oxide in water, adjust the pH with ammonia water, prepare a slurry in a certain proportion, and obtain a graphene oxide film by scraping and drying. The pH is 5-10, the mass fraction of the slurry is 2-7%, the coating thickness is 0.5-5.0 mm, and the drying temperature is 40-105°C; preferably, the pH is 6-8, the mass fraction is 4-5%, the coating thickness is 2.5-3.5 mm, and the drying temperature is 60-80°C.

[0045] (3) Heat-treating the composite film of step (2) to remove the functional groups and inorganic salts in the graphene oxide, repair the internal defects and conjugated structure of the graphene, and obtain a graphene foam film. The heat treatment includes three stages: low temperature (80-400°C), medium temperature (carbonization, 800-1500°C) and high temperature (graphitization, 2700-3200°C). The heating rate, insulation time and atmosphere conditions corresponding to different temperatures are different. The heating rate in the low temperature stage is 0.5-5°C / min, insulation time is 30-120min, and the atmosphere is air or nitrogen; the heating rate in the medium temperature stage is 1-20°C / min, insulation time is 30-240min, and the atmosphere is one of nitrogen, argon, and hydrogen-argon mixed gas; the heating rate in the high temperature stage is 1-20°C / min, insulation time is 30-600min, and the atmosphere is argon. Preferably, the low-temperature heat treatment temperature is 200-300°C, the heating rate is 0.5-1°C / min, the insulation time is 60-90min, and the atmosphere is air; the carbonization temperature is 850-1050°C, the heating rate is 5-8°C / min, the insulation time is 60-120min, and the atmosphere is a hydrogen-argon mixture with a hydrogen ratio of 5-10%; the graphitization temperature is 3000-3200°C, the heating rate is 3-6°C / min, the insulation time is 120-180min, and the atmosphere is argon.

[0046] (4) Calendering the graphene foam film of step (3) to increase the material density and obtain a graphene composite film. The calendering process includes one or more of roller pressing and flat pressing, and the pressure is 10-200 MPa. By using different calendering methods and repeated calendering, it is ensured that the density of the composite film meets the requirements.

[0047] The present invention not only solves the problem that traditional CVD graphene films are thin and cannot be used commercially on a large scale, but also improves the thermal conductivity of redox graphene films, giving full play to the intrinsic properties of graphene materials and making them more competitive in the market.

[0048] Another aspect of the embodiments of the present invention further provides a graphene composite film with high thermal conductivity obtained by the aforementioned preparation method.

[0049] In some preferred embodiments, the graphene composite film has a thickness of 20-120 μm.

[0050] In some preferred embodiments, the thermal conductivity of the graphene composite film is 1650-1950 W / mK.

[0051] In some preferred embodiments, the characteristic size Lc of graphite crystallites in the graphene composite film is 50-80 nm.

[0052] Another aspect of the embodiments of the present invention further provides the use of the aforementioned graphene composite film with high thermal conductivity in the fields of electronic heat dissipation, aerospace, medical equipment or new energy.

[0053] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0054] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0055] Example 1 (1) Preparation of CVD graphene film: A copper-nickel alloy foil (copper mass fraction 90%) was selected as the graphene growth substrate. The foil with a thickness of 20 μm was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 35 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained ( Figure 2 ); (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 5.0%, and the pH value is 6.5; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260 °C at a heating rate of 0.5 °C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900 °C at a heating rate of 5 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3100 °C at a heating rate of 5 °C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 51 μm and the density was 2.23 g / cm 3 , thermal conductivity 1943 W / mK, graphite crystallite size Lc=78.9 nm, the cross-sectional scanning electron microscope image of the graphene composite film in this embodiment is as follows Figure 4 shown.

[0056] Comparative Example 1 (Single-layer CVD graphene template) (1) Preparation of CVD graphene film: Copper foil was selected as the graphene growth substrate. A 20 μm thick copper foil was cut into 10*6 cm foils and placed in a tubular furnace. A hydrogen-argon mixed gas (10% hydrogen) was introduced and the tubular furnace was heated to 900°C to pretreat the copper foil. The temperature was kept at this temperature for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced to grow graphene. The flow rates were 20 sccm and 25 sccm, respectively, and the ventilation time was 12 min. After that, the heating and introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a single layer of CVD graphene film was obtained ( Figure 3 ); (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 5.0%, and the pH value is 6.2; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 4 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260 °C at a heating rate of 0.5 °C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900 °C at a heating rate of 5 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 2950 °C at a heating rate of 5 °C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene thermal conductive film. The thickness of the graphene thermal conductive film was measured to be 40 μm and the density was 2.12 g / cm 3 , thermal conductivity 1613 W / mK, graphite crystallite size Lc=49.1 nm.

[0057] Comparative Example 2 (without using CVD graphene template) (1) Preparation of graphene oxide film: a certain amount of graphene oxide was dispersed in deionized water, and the pH value was adjusted with ammonia water to prepare a graphene oxide slurry, wherein the solid mass percentage of the slurry was 5.0% and the pH value was 6.5; the slurry was scraped onto a PET substrate with a coating thickness of 5 mm, and dried at 60° C. for 8 hours to obtain a graphene oxide film; (2) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 200 °C at a heating rate of 0.5 °C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 1100 °C at a heating rate of 5 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3000 °C at a heating rate of 5 °C / min, keeping warm for 120 min, to obtain graphene foam film; (3) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 50 MPa using a flat pressing device to obtain a graphene thermal conductive film. The density of the graphene thermal conductive film was measured to be 2.10 g / cm 3 , thermal conductivity 1580 W / mK, graphite crystallite size Lc=48.2 nm.

[0058] Comparative Example 3 (1) Preparation of CVD graphene film: Nickel foil was selected as the graphene growth substrate. A nickel foil with a thickness of 25 μm was cut into 10*6 cm foils and placed in a tubular furnace. A hydrogen-argon mixed gas (20% hydrogen) was introduced and the tubular furnace was heated to 1010°C to pretreat the foil, and the temperature was kept for 60 min. The tubular furnace was then heated to 1050°C, and carbon source gas acetylene and inert gas argon were introduced for graphene growth. The flow rates were 25 sccm and 35 sccm, respectively, and the ventilation time was 18 min. After that, the heating and the introduction of the carbon source gas were stopped, and after the tubular furnace was cooled down, a metal foil containing only multilayer CVD graphene films was obtained, with the number of layers being 2-4. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 4.5%, and the pH value is 7.2; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260°C at a heating rate of 0.5°C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900°C at a heating rate of 5°C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3050°C at a heating rate of 5°C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene thermal conductive film. The thickness of the graphene thermal conductive film was measured to be 45 μm and the density was 2.10 g / cm 3 , thermal conductivity 1575 W / mK, graphite crystallite size Lc=45.7 nm.

[0059] Comparative Example 4 (1) Preparation of CVD graphene film: A copper-nickel alloy foil (copper mass fraction 90%) was selected as the graphene growth substrate. The foil with a thickness of 20 μm was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 115 sccm and 60 sccm, respectively, and the ventilation time was 20 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, the metal foil of the CVD graphene film was obtained. Due to the excessive gas flow rate and ventilation time, the graphene film had no pagoda-like structure and was a multilayer graphene film. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 5.0%, and the pH value is 6.5; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260°C at a heating rate of 0.5°C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900°C at a heating rate of 5°C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3050°C at a heating rate of 5°C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 50 μm and the density was 2.10 g / cm 3 , thermal conductivity 1546 W / mK, graphite crystallite size Lc=44.3 nm.

[0060] Example 2 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 80%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. Argon gas was introduced and the tubular furnace was heated to 900°C to pretreat the foil, and the temperature was kept for 120 min. The tubular furnace was then heated to 1010°C, and carbon source gas acetylene and inert gas argon were introduced for graphene growth. The flow rates were 20 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped, and after the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 4.0%, and the pH value is 6.5; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260°C at a heating rate of 0.5°C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900°C at a heating rate of 5°C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3000°C at a heating rate of 5°C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 41 μm and the density was 2.19 g / cm 3 , thermal conductivity 1760 W / mK, graphite crystallite size Lc=68.4 nm.

[0061] Example 3 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 90%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 35 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 7.0%, and the pH value is 7.5; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 90°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 350 °C at a heating rate of 0.5 °C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900 °C at a heating rate of 5 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3100 °C at a heating rate of 5 °C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 130 MPa using a flat press to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 80 μm and the density was 2.12 g / cm 3 , thermal conductivity 1687W / mK, graphite crystallite size Lc=62.7 nm.

[0062] Example 4 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 90%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 35 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 4.5%, and the pH value is 8.2; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 4 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260°C at a heating rate of 0.5°C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 1300°C at a heating rate of 10°C / min, keeping warm for 120 min; high temperature graphitization, in argon atmosphere, heating up to 3050°C at a heating rate of 5°C / min, keeping warm for 180 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 35 μm and the density was 2.20 g / cm 3, thermal conductivity 1862 W / mK, graphite crystallite size Lc=73.5 nm.

[0063] Example 5 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 90%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 35 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 6.0%, and the pH value is 6.3; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 60°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 380°C at a heating rate of 1.5°C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900°C at a heating rate of 5°C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 2850°C at a heating rate of 5°C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 60 times at a pressure of 45 MPa using a roller pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 62 μm and the density was 2.14 g / cm 3 , thermal conductivity 1671 W / mK, graphite crystallite size Lc=51.6 nm.

[0064] Example 6 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 85%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 15%) was introduced and the tubular furnace was heated to 980°C to pretreat the foil and kept warm for 30 min. Then, the temperature was kept constant and carbon source gas ethanol and inert gas argon were introduced for graphene growth. The flow rates were 65 sccm and 25 sccm, respectively, and the ventilation time was 10 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 3.0%, and the pH value is 6.5; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 3 mm, and dried at 45°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 260 °C at a heating rate of 0.5 °C / min, keeping warm for 60 min; medium temperature carbonization, in argon atmosphere, heating up to 900 °C at a heating rate of 5 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3100 °C at a heating rate of 5 °C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 45 MPa using a flat press to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 22 μm and the density was 2.20 g / cm 3 , thermal conductivity 1820 W / mK, graphite crystallite size Lc=71.9 nm.

[0065] Example 7 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 90%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 35 sccm and 25 sccm, respectively, and the ventilation time was 15 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 5.0%, and the pH value is 8.2; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 5 mm, and dried at 75°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 300 °C at a heating rate of 2.0 °C / min, keeping warm for 30 min; medium temperature carbonization, in argon atmosphere, heating up to 1000 °C at a heating rate of 10 °C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 2900 °C at a heating rate of 12 °C / min, keeping warm for 480 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 20 times at a pressure of 70 MPa using a flat press to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 53 μm and the density was 2.18 g / cm 3 , thermal conductivity 1795 W / mK, graphite crystallite size Lc=63.7 nm.

[0066] Example 8 (1) Preparation of CVD graphene film: A copper-nickel alloy (copper mass fraction 90%) was selected as the graphene growth substrate. A 20 μm thick foil was cut into 10*6 cm sheets and placed in a tubular furnace. A hydrogen-argon mixed gas (hydrogen 10%) was introduced and the tubular furnace was heated to 900°C to pretreat the foil and kept warm for 120 min. The tubular furnace was then heated to 960°C and carbon source gas ethylene and inert gas argon were introduced for graphene growth. The flow rates were 25 sccm and 45 sccm, respectively, and the ventilation time was 25 min. After that, the heating and the introduction of the carbon source gas were stopped. After the tubular furnace was cooled down, a metal foil containing a multi-point pagoda-shaped CVD graphene film was obtained. (2) Preparation of graphene / graphene oxide composite film: First, prepare graphene oxide slurry, take a certain amount of graphene oxide and disperse it in deionized water, adjust the pH value with ammonia water, the solid mass percentage of the slurry is 3.5%, and the pH value is 9.6; then, the prepared graphene oxide slurry is scraped on the side of the metal foil containing CVD graphene, the coating thickness is 4 mm, and dried at 85°C for 8 hours to obtain a graphene / graphene oxide composite film; (3) Heat treatment of composite film: low temperature heat treatment, in air atmosphere, heating up to 180°C at a heating rate of 1.0°C / min, keeping warm for 90 min; medium temperature carbonization, in argon atmosphere, heating up to 1050°C at a heating rate of 8°C / min, keeping warm for 60 min; high temperature graphitization, in argon atmosphere, heating up to 3100°C at a heating rate of 5°C / min, keeping warm for 120 min, to obtain graphene foam film; (4) Calendering treatment: The graphene foam film was repeatedly pressed 30 times at a pressure of 70 MPa using a flat pressing device to obtain a graphene composite film. The thickness of the graphene composite film was measured to be 33 μm and the density was 2.22 g / cm 3 , thermal conductivity 1901 W / mK, graphite crystallite size Lc=74.2 nm.

[0067] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0068] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a graphene composite film with high thermal conductivity, characterized in that: include: A graphene film is prepared on a copper-nickel alloy substrate by a CVD method; wherein the graphene film comprises a single-layer graphene structure and a pagoda-shaped multi-layer graphene core structure dispersed on the surface of the single-layer graphene structure; applying a graphene oxide slurry to the surface of the graphene film to form a graphene / graphene oxide composite film; Furthermore, the graphene / graphene oxide composite film is subjected to carbonization, graphitization and calendering treatment to obtain a graphene composite film with high thermal conductivity.

2. The preparation method according to claim 1, characterized in that: Specifically include: Placing a copper-nickel alloy substrate in a tube furnace, introducing a first atmosphere, and pre-treating the substrate at 800-1100° C. for 10-200 min; wherein the first atmosphere comprises any one of hydrogen, argon, and a hydrogen-argon mixed gas; and the gas flow rate of the first atmosphere is 10-500 sccm; And, a carbon source gas and an inert gas are introduced into the device and graphene is deposited and grown on the substrate surface at 800-1100° C. for 1-30 minutes, thereby obtaining a graphene film; wherein the flow rate of the carbon source gas is 1-100 sccm, and the flow rate of the inert gas is 0.5-100 sccm.

3. The preparation method according to claim 2, characterized in that: The copper content in the copper-nickel alloy substrate is 50-98wt%; and / or, the bottom layer diameter of the pagoda-shaped multilayer graphene core structure is 0.1-5 mm; and / or, the height of the pagoda-shaped multilayer graphene core structure is 1.3-3.4 nm; And / or, when the first atmosphere is a hydrogen-argon mixture, the volume content of hydrogen in the first atmosphere is 1-80%; And / or, the carbon source gas includes any one or more of ethylene, propylene, acetylene, methane, and ethanol; And / or, the inert gas includes any one or more combinations of nitrogen, argon and helium.

4. The preparation method according to claim 1, characterized in that: Specifically include: Mixing graphene oxide with water and adjusting the pH value to 5-10 with ammonia water to form graphene oxide slurry; wherein the solid content in the graphene oxide slurry is 2-7wt%; And, the graphene oxide slurry is coated on the surface of the graphene film and dried at 40-105° C. to obtain a graphene / graphene oxide composite film, wherein the coating thickness coated on the surface of the graphene film is 0.5-5.0 mm.

5. The preparation method according to claim 4, characterized in that: The pH value is 6-8; and / or the solid content of the graphene oxide slurry is 4-5wt%; And / or, the drying temperature is 60-80° C.; and / or, the coating thickness is 2.5-3.5 mm.

6. The preparation method according to claim 1, characterized in that: Specifically include: The temperature is raised to 80-400°C at a heating rate of 0.5-5°C / min, and the graphene / graphene oxide composite film is subjected to low-temperature treatment in a low-temperature atmosphere for 30-120min, then the temperature is raised to 800-1500°C at a heating rate of 1-20°C / min, and a carbonization treatment is performed in a medium-temperature atmosphere for 30-240min, and then the temperature is raised to 2700-3200°C at a heating rate of 1-20°C / min, and a graphitization treatment is performed in a high-temperature atmosphere for 30-600min; wherein the low-temperature atmosphere includes air and / or nitrogen; the medium-temperature atmosphere includes any one or more combinations of nitrogen, argon, and a hydrogen-argon mixture; and the high-temperature atmosphere includes argon.

7. The preparation method according to claim 6, characterized in that: The heating rate of the low temperature treatment is 0.5-1°C / min; and / or, the temperature of the low temperature treatment is 200-300°C; and / or, the time of the low temperature treatment is 60-90min; and / or, the low temperature atmosphere includes air; and / or, the heating rate of the carbonization treatment is 5-8°C / min; and / or, the temperature of the carbonization treatment is 850-1050°C; and / or, the time of the carbonization treatment is 60-120min; and / or, the medium temperature atmosphere comprises a hydrogen-argon mixture, wherein the volume content of hydrogen in the hydrogen-argon mixture is 5-10%; And / or, the heating rate of the graphitization treatment is 3-6°C / min; and / or, the temperature of the graphitization treatment is 3000-3200°C; and / or, the time of the graphitization treatment is 120-180min.

8. The preparation method according to claim 1, characterized in that: The calendering treatment adopts a method including roller pressing and / or flat pressing; And / or, the pressure used in the calendering treatment is 10-200 MPa.

9. A graphene composite film with high thermal conductivity obtained by the preparation method according to any one of claims 1 to 8; Preferably, the thickness of the graphene composite film is 20-120 μm; preferably, the thermal conductivity of the graphene composite film is 1650-1950 W / mK; preferably, the characteristic size Lc of graphite crystallites in the graphene composite film is 50-80 nm.

10. Use of the graphene composite film with high thermal conductivity as claimed in claim 9 in the fields of electronic heat dissipation, aerospace, medical equipment or new energy.

Citation Information

Cited By

  • Preparation method of graphene film with high longitudinal heat-conducting property

    CN119976815A

  • Method for repairing defects of high-thermal-conductivity porous graphite structure and improving graphitization degree through graphene

    CN120534966A

  • Heat dissipation-flame retardant integrated flexible multifunctional composite film as well as preparation method and application thereof

    CN122301526A